The Implementation of Problem Based Learning Model on Science Problem Solving Ability of Elementary School Students - Rahmani, Rahmani; Mahyana, Mahyana (Universitas Serambi Mekkah, 2021)
This study aims to describe students' science problem solving abilities after the application of the Problem Based Learning model. The hypothesis formulated in this research is the implementation of Problem Based Learning (PBL) learning model can improve the science problem solving ability of elementary school students. The approach used in this research is a quantitative approach. The type of research used in this study is a quasi-experimental research. The research design used in this study is one group pretest posttest design. The population of this study was all high-class students at SD Negeri 5 Banda Aceh for the 2020/2021 academic year, totaling 170 students. The sampling technique used was random sampling. Based on the results of the lottery, the samples used were students of class IV-B, totaling 16 boys and 10 girls. Data collection techniques in this study used tests in the form of pretest and posttest. Data analysis technique used was N-Gain. Based on the data analysis, the average pretest and posttest values were 35.54 and 73, respectively, with an N-Gain of 0.59 in the